2016
DOI: 10.1096/fj.201600611r
|View full text |Cite
|
Sign up to set email alerts
|

Role of neutral ceramidase in colon cancer

Abstract: Alterations in sphingolipid metabolism, especially ceramide and sphingosine 1-phosphate, have been linked to colon cancer, suggesting that enzymes of sphingolipid metabolism may emerge as novel regulators and targets in colon cancer. Neutral ceramidase (nCDase), a key enzyme in sphingolipid metabolism that hydrolyzes ceramide into sphingosine, is highly expressed in the intestine; however, its role in colon cancer has not been defined. Here we show that molecular and pharmacological inhibition of nCDase in col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 57 publications
7
69
0
Order By: Relevance
“…NCDase is highly abundant in intestinal tissues, and inhibition of NCDase resulted in ceramide-mediated apoptosis and autophagy in colon cancer cells and tumour xenograft mouse models 70 . Moreover, NCDase-null mice were protected from the development of AOM-induced colon cancer 70 .…”
Section: Sphingolipid Metabolism and Cancermentioning
confidence: 99%
“…NCDase is highly abundant in intestinal tissues, and inhibition of NCDase resulted in ceramide-mediated apoptosis and autophagy in colon cancer cells and tumour xenograft mouse models 70 . Moreover, NCDase-null mice were protected from the development of AOM-induced colon cancer 70 .…”
Section: Sphingolipid Metabolism and Cancermentioning
confidence: 99%
“…This study also demonstrated that inhibition of NC in a xenograft model delayed tumor growth and increased ceramide. Importantly, mice lacking NC treated with the pro-carcinogen azoxymethane were protected from tumor formation (Garcia-Barros et al, 2016). These results suggest that NC may emerge as a therapeutic target in colon cancer.…”
Section: Neutral Ceramidase (Asah2 Asah2b Asah2c)mentioning
confidence: 99%
“…62 RNAi targeting of ASAH2 in HT29 and HCT116 colon cancer cell lines increases ceramide, leading to 50% loss in viability in vitro and delayed xenograft growth in vivo. 63 In the AOM carcinogenesis model, ASAH2-deficient mice developed significantly fewer tumors with a 93% reduction in adenocarcinomas and an 82% decrease in total colon tumors compared with wild type mice. 63…”
Section: Ceramidasesmentioning
confidence: 96%
“…63 In the AOM carcinogenesis model, ASAH2-deficient mice developed significantly fewer tumors with a 93% reduction in adenocarcinomas and an 82% decrease in total colon tumors compared with wild type mice. 63…”
Section: Ceramidasesmentioning
confidence: 96%